Operations management - Stevenson, William J. (Boston : McGraw-Hill Irwin, 2002)
This text surveys the field of operations in both the services and manufacturing sectors. Provides enhanced coverage from the strategies of designing a product or service, through the processes and systems of making and delivering the product, and controlling the operations. It is intended as an introduction to the field of operations management. It is suitable for both undergraduate and graduate students.
Includes indexes.
oif 10/10/14
Loan
Keywords: Production management; Operations management; Management science